INTRODUCTION OF DEVICES AND ASSEMBLING COMPUTERS TO STUDENTS - Halim, Apriyanto; Ulina, Mustika; Joosten, Joosten (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
SMK Swasta Methodist Tanjung Morawa is a private school under the auspices of the Kasih Imanuel Indonesia Methodist Foundation, which was established in 2008. SMK Swasta Methodist Tanjung Morawa has various majors, one of which is Network and Computer Engineering (TKJ). Assembling computer equipment is one of the subjects that can help students become more familiar with computer equipment and know how to fix it and of course this lesson is already a lesson that is in accordance with the majors of SMK Swasta Methodist Tanjung Morawa students, namely Computer Network Engineering (TKJ). The students have studied theoretically related to assembling computer equipment, therefore, the Faculty of Informatics, Universitas Mikroskil offers activities in the form of training in assembling computer equipment to improve students' ability to have good knowledge in computer equipment and how to assemble it. This training activity lasted for 2 days and was carried out in the accounting laboratory at Universitas Mikroskil. During this training activity the students were given pre-test questions, materials and case studies, post-tests and final feedback.